Taxonomy of some little-understood North American ants (Hymenoptera: Formicidae) - Shattuck, Steve; Cover, Stefan (Zootaxa, 2016)
The North American ant fauna has a long and detailed taxonomic history, and the fauna is relatively well characterized compared with those of many other regions. The vast majority of taxon names are clearly defined, being treated as either valid or invalid (primarily junior synonyms). Because of this, though considerable revisionary work will be necessary in the future, specimens collected from this region may often be placed with reasonable confidence either to species, or in some cases, to species complexes even if the status of the specific taxa involved are uncertain.